220k views
4 votes
Use the following problem to answer the question below:

Given: m∠ABE = m∠CBD Prove: m∠ABD = m∠CBE

What is the reason for D?

Use the following problem to answer the question below: Given: m∠ABE = m∠CBD Prove-example-1
User Jubei
by
5.1k points

1 Answer

3 votes

Answer:

m∠ABD = m∠CBE ⇒ by subtracting a common angle from the given angles

Explanation:

∵ m∠ABE = m∠CBD

∵ m∠ABD = m∠ABD + m∠DBE

∵ m∠CBD = m∠CBE + m∠EBD

∵ ∠EBD is common angle between them

∴ m∠ABD = m∠CBE

User Kushagra
by
5.2k points